2007
DOI: 10.3382/ps.2007-00134
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Selection for Ascites Incidence in Chickens

Abstract: Chicken lines that were either resistant or susceptible to ascites syndrome were developed by using a hypobaric chamber to induce the disease. Birds were reared in a hypobaric chamber that simulated high altitude by operating under a partial vacuum, which thereby lowered the partial pressure of oxygen. Ascites mortality data from birds reared under hypobaric chamber conditions were used to select siblings to be used for breeding. The response to selection for the susceptible (SUS) and resistant (RES) lines of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 26 publications
2
80
0
Order By: Relevance
“…Most broilers that remained healthy under the high-challenge AICs exhibited the same early GR and BW as those that later developed AS. These results, and the relatively high incidence of AS in the slow-growing line, indicated that there is very little, if any, direct genetic association between AS and genetic differences in potential GR, which suggests that AS-resistant broilers can be selected for higher GR These results, supported by several previous studies [68,[70][71][72][73][74][75][76][77][78], suggest that there is no "true" genetic correlation between the potential GR of broilers and their propensity to develop AS. It seems that AS is not caused by the increased O2 requirement of a fast growth rate, but by an impairment of the O2 supply needed to sustain the fast growth rate.…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…Most broilers that remained healthy under the high-challenge AICs exhibited the same early GR and BW as those that later developed AS. These results, and the relatively high incidence of AS in the slow-growing line, indicated that there is very little, if any, direct genetic association between AS and genetic differences in potential GR, which suggests that AS-resistant broilers can be selected for higher GR These results, supported by several previous studies [68,[70][71][72][73][74][75][76][77][78], suggest that there is no "true" genetic correlation between the potential GR of broilers and their propensity to develop AS. It seems that AS is not caused by the increased O2 requirement of a fast growth rate, but by an impairment of the O2 supply needed to sustain the fast growth rate.…”
Section: Introductionsupporting
confidence: 76%
“…That study demonstrated the feasibility of selection based on mortality of AS-susceptible individuals under a protocol of high-challenge AIC. Divergent selection for AS mortality was conducted by Anthony et al [78]: the AS was induced in a hypobaric chamber where oxygen content was reduced to the level equivalent to 2,900 m above sea level. After 10 generations of divergent sire-family selection, %AS increased to about 90% in the AS-susceptible line and decreased to about 20% in the ASresistant line, thus reaching a divergence of about 70% [78].…”
Section: Direct Selection Against Susceptibility To Asmentioning
confidence: 99%
See 1 more Smart Citation
“…Ascites has become a major cause of mortality in modern broiler production worldwide (Wideman & French, 2000;Balog, 2003;Pakdel et al, 2005;Pavlidis et al, 2007;Arce-Menocal et al, 2009;Hassanzadeh et al, 2010). Many difficulties in broiler production, such as ascites, are related with cardiovascular development and function problems (Leksrisompong et al, 2007).…”
Section: The Effects Of Different Eggshell Temperatures Between Embrymentioning
confidence: 99%
“…Pulmonary hypertension (PH) in modern genetic strains of chicken broilers is a world wide distributed entity, which has a recognized economical impact (Maxwell et al, 1997;Pavlidis et al, 2007). Also, the commercial chicken has been a model to study PH in man, because encountered pathological changes in that animal closely resemble the human condition.…”
Section: Introductionmentioning
confidence: 99%